2024
DOI: 10.1039/d4ya00056k
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic and plasmonic Ag and Cu integrated TiO2 thin films for enhanced solar hydrogen production in direct sunlight

Sunesh S. Mani,
Sivaraj Rajendran,
Pushkaran S. Arun
et al.

Abstract: Plasmonic metal nanoparticle integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag-Cu/TiO2), prepared by a simple chemical reduction method, has been demonstrated to show superior activity in thin-film form for solar...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The excellent catalytic performance of Pd/TiO 2 , 165 Ag/TiO 2 , 43 Cu–Ni/TiO 2 , 3 Cu x O/TiO 2 , 209 Cu–Ag/TiO 2 206 and AuPd/C/TiO 2 66 fabricated in thin-film form compared to their powder counterparts has been demonstrated in the literature. Tudu et al reported that the thin film form of the Cu–Ni/TiO 2 (1 : 1 = Cu : Ni) photocatalyst exhibited an enhanced rate of hydrogen evolution (41.7 mmol h −1 g −1 ) compared to its powder form (1.75 mmol h −1 g −1 ) due to the efficient charge generation and its utilization in the film form, which mimicked the natural photosynthesis by green leaves.…”
Section: Factors Influencing Solar Hydrogen Generation Activity Of Tio2mentioning
confidence: 83%
See 1 more Smart Citation
“…The excellent catalytic performance of Pd/TiO 2 , 165 Ag/TiO 2 , 43 Cu–Ni/TiO 2 , 3 Cu x O/TiO 2 , 209 Cu–Ag/TiO 2 206 and AuPd/C/TiO 2 66 fabricated in thin-film form compared to their powder counterparts has been demonstrated in the literature. Tudu et al reported that the thin film form of the Cu–Ni/TiO 2 (1 : 1 = Cu : Ni) photocatalyst exhibited an enhanced rate of hydrogen evolution (41.7 mmol h −1 g −1 ) compared to its powder form (1.75 mmol h −1 g −1 ) due to the efficient charge generation and its utilization in the film form, which mimicked the natural photosynthesis by green leaves.…”
Section: Factors Influencing Solar Hydrogen Generation Activity Of Tio2mentioning
confidence: 83%
“…165,206,207 The catalyst nanoparticles assembled in thin film are nearly uniformly spread across the substrate and have a large exposed surface area to the reactants and irradiation, resulting in more efficient interactions among the catalyst particles, light and reactants with relatively less mass transfer constraints. The possible reasons for the enhanced solar hydrogen evolution activity of photocatalysts fabricated in thin film form are as follows: 206 (1) by optimizing the film thickness to around 10 μm, the light absorption achieved is the maximum in thin films, while the same material in suspension form scatters light, rather than absorbing it; (2) the exposure of the maximum surface to solar radiation in thin film form is beneficial for enhancing the light-harvesting and light-induced electron excitation processes and increases the hydrogen production and apparent quantum yield (AQY); (3) the maximum utilization of surface area and active sites is possible in thin film form, which is good for the diffusion of charges toward the reaction sites; (4) better contact of catalyst nanoparticles is possible in the film form, which enhances the charge separation and charge utilization, whereas charge recombination is severe in powder form; and (5) thin film form with some surface roughness is beneficial for the internal scattering of light within the depth of thin films and enhances the charge carrier production/utilization. In powder form, additional energy in the form of electricity is needed for constant stirring to make the catalyst particles highly homogeneous in the reaction medium.…”
Section: Factors Influencing Solar Hydrogen Generation Activity Of Tio2mentioning
confidence: 99%